PENERAPAN E-CR PADA PENGEMBANGAN PROTOTIPE DATA CENTER (STUDI KASUS: UNIT PELAYANAN TEKNIS TEKNOLOGI INFORMASI DAN KOMUNIKASI UNIVERSITAS PENDIDIKAN GANESHA). - Dermawan, Kadek Teguh; Putrama, I Made; Darmawiguna, I Gede Mahendra (Jurnal Nasional Pendidikan Teknik Informatika : JANAPATI, 2018)
Interoperability is a component that contains information systems integration. It?s provide an interfaces from multiple data sources to support data and information integrity between various information systems. This study aims: (1) Creating the design and implementation of Data Center System to support data integration by implementing ETL Process, cryptopost, and rest service. (2) Present a prototype Data Center review to support data integrase by implementing ETL Process, cryptopost, and rest service. This research is expected to provide solution of data integration model between information system running on HTTP protocol. The integration model uses synchronous and asychronous schemes. This type of research is research and development (Research and Development) with Agile SCRUM Framework research model. For the testing process, two (2) test process stages are performed: (1) whitebox and (2) blackbox testing.